Mechanical and physical properties of dentine-glass composites - (:unkn) unknown (Trans Tech Publications Ltd, 2017)
Hydroxyapatite (HA) is one of the most widely used bioceramics to reconstruct most parts of the skeleton. HA biomaterials are nontoxic and biocompatible with bony tissues. It can be derived from natural sources like bovine bone and other original sources. Also it can be produced synthetically from reagent materials. Due to the fact that HA is not able to be used in biomedical applications cause of bear loadings. It has to be reinforced with materials such as whiskers, metallic oxides, glasses and others. In this study, sintering effects on physical and mechanical properties, such as density (gr/cm3), compression strength (MPa) and Vickers microhardness (HV) of the commercial inert glass (CIG) added human dentine HA (DHA) composite investigated. HA source material is dentine material which is obtained from extracted human teeth. After calcinations enamel and dentine parts were separated (850°C - 4 hours). DHA particles were ball milled and sieved through 100μm sieve. DHA is mixed with 5 and 10 % CIG. Then, this composite material is pressed with a steel mould and sintered in the temperature range of 1000°C to 1300°C with 100°C increments. After scanning electron microscope (SEM) and x-ray diffraction (XRD) studies, both physical and mechanical characterization for DHA - CIG composites are completed by performing density, micro and macro-mechanical test procedures, i.e., HV and compression testing. Briefly, density measurements are conducted corresponding to the Archimedes principle. HV measurements are obtained under a 200g load. Compression test is performed at a rate of 2 mm/min. Here the densest structure was obtained as 2.48 gr/cm3 at 1300°C with 5 wt.% CIG addition. The HV values are increasing with temperature (1082 HV at 1300°C with 10 wt.% CIG addition). The toughest MPa value is 118MPa with 10%CIG addition, sintered at 1300°C. Inert glass addition to dentine HA sounds promising with increasing values of microhardness and compression properties. It can be described as a very hard and a strong biomaterial. © 2017 Trans Tech Publications.
Keywords: Commercial inert glass; Composites; Dentine hydroxyapatite; Hydroxyapatite